(untitled) (AYUSHDHARA, 2024)
Autism spectrum disorder includes a group of neurodevelopmental disorders, which disrupts normal functioning of the brain and impairs communication, social interaction, emotional balance with the presence of repetitive stereotypic mannerisms. Underlying etiology of autism spectrum disorder is still unknown. Studies on genetic causes, immune system dysregulation, inflammation, exposure to environmental toxicants, defective gut microbiome are still continuing. In ayurveda, most psycho social abnormalities are included in the category of Unmada. Along with other etiological factors, impaired digestive and metabolic functions are postulated as the root cause of Unmada. And in accord with the gut brain axis, systemic accumulation of metabolic wastes also disrupts the functional integrity of the brain. The present study describes the case of a child with ASD with hyperactivity, who has been clinically diagnosed and treated with Ayurvedic medications, Sneha sweda therapies and diet modifications, which helps in maintaining the healthy functioning of the brain. Within 3 months of intervention, the child became symptomatically better. Case study briefs Ayurvedic concepts and Ayurvedic treatment protocols regarding ASD.